2020
DOI: 10.3389/fphar.2020.01175
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B Inhibits Osteoclastogenesis and Protects Against Ovariectomy-Induced Bone Loss

Abstract: Osteoporosis is a systemic skeletal disease which is highly prevalent worldwide and considered to be associated with excessive bone resorption mediated by osteoclast. Osteoclast differentiation is featured by the activation of inflammation-related pathways and the generation of reactive oxygen species. Schisandrin B is a bioactive compound with strong antiinflammation and antioxidative properties, we thus speculated that Schisandrin B might serve as a potential candidate for osteoporosis. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…The characteristics of multi-targeting traditional Chinese medicine extracts with fewer and less severe side-effects in the treatment of tumors has attracted increased attention ( 32 ). Amongst these agents, Sch B has been shown to exert therapeutic effects in a variety of malignant tumors, and recent reports have demonstrated that Sch B may inhibit osteoclast formation and function, highlighting Sch B as a potential drug for OS treatment ( 7 – 11 , 33 ). In the present study, it was revealed that Sch B exerted inhibitory effects on OS in vitro and in vivo via Wnt/β-catenin and PI3K/Akt signaling pathway regulation; SchB inhibited the proliferation, migration and invasion, and promoted the apoptosis of OS cells; it also inhibited the tumor growth and reduced the lung metastasis of OS in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of multi-targeting traditional Chinese medicine extracts with fewer and less severe side-effects in the treatment of tumors has attracted increased attention ( 32 ). Amongst these agents, Sch B has been shown to exert therapeutic effects in a variety of malignant tumors, and recent reports have demonstrated that Sch B may inhibit osteoclast formation and function, highlighting Sch B as a potential drug for OS treatment ( 7 – 11 , 33 ). In the present study, it was revealed that Sch B exerted inhibitory effects on OS in vitro and in vivo via Wnt/β-catenin and PI3K/Akt signaling pathway regulation; SchB inhibited the proliferation, migration and invasion, and promoted the apoptosis of OS cells; it also inhibited the tumor growth and reduced the lung metastasis of OS in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting revealed that Sch B could inhibit OS cell migration and invasion by inhibiting EMT. In addition, it has been demonstrated that Sch B inhibits osteoclastogenesis ( 33 ). In primary bone cancer and metastasis, the process of bone remodeling creates a favorable environment for the establishment and progression of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of natural extracts or compounds with beneficial effects on osteoporosis is opening a new road toward a sustainable approach to the disease [ 40 ]. Most of them specifically exhibit antioxidant and anti-inflammatory properties, which attenuate the bone-loss phenotype in vivo [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no study concerning the specific mechanism of Schisandrin B in attenuating pyroptosis. Meanwhile, there is also no study on Schisandrin B in relieving sepsis-induced colitis by regulating pyroptosis [ 29 , 30 ]. Additionally, Schisandrin B has also been revealed to play a protective role in arthritis [ 31 ].…”
Section: Introductionmentioning
confidence: 99%